EFEKTIVITAS PROGRAM BANTUAN LANGSUNG TUNAI (BLT) DANA DESA BAGI MASYARAKAT MISKIN TERKENA DAMPAK COVID-19 DI DESA JALUR PATAH KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2020-2021 - Muhamad Ilham; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
BLT-Dana Desa is one of the programs issued by the Indonesian government to overcome the impact of economic factors on people affected by the Covid-19 pandemic in the form of financial assistance provided to the poor and families affected by the Covid-19 pandemic. The BLT-DD program was issued by the government in order to overcome declining public finances due to the Covid-19 outbreak. This study aims to determine the effectiveness of the BLT-DD program during the covid-19 period in the village of Jalan Patah, Sentajo Raya District, Kuantan Singingi Regency and to determine the factors that hinder the effectiveness of the BLT-DD program in its implementation. The theory used in this study is the theory of program effectiveness by Edy Sutrisno using five indicators to measure program effectiveness (understanding of the program, right on target, on time, achieving goals and real change). To answer these problems, researchers used a descriptive qualitative approach. The results of this study explain that the implementation of the BLT- DD program in the village of Jalur Patah, Sentajo Raya District, Kuantan Singingi Regency is still not effective. Evidenced by the Village Government not being optimal in their duties in determining the target criteria for the BLT-DD program so that there are still people who have not been recorded for BLT-DD receipts. It is hoped that before launching the policy, the government can socialize the program so that related parties understand the purpose of the BLT-DD program. Keywords: Program Understanding, On Target, On Time, Achievement Of Goals And Real Change